2020
DOI: 10.1002/rev3.3226
|View full text |Cite
|
Sign up to set email alerts
|

Habit formation limits growth in teacher effectiveness: A review of converging evidence from neuroscience and social science

Abstract: Teachers become rapidly more effective during the early years of their career but tend to improve increasingly slowly thereafter. This article reviews and synthesises converging evidence from neuroscience, psychology, economics and education suggesting that teachers’ rate of growth slows because their practice becomes habitual. First, we review evidence suggesting that teaching is highly conducive to habit formation and that teachers display characteristic features of habitual behaviour. Next, we review empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 112 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…Adopting a different approach was not easy. This is unsurprising given that teaching is highly conducive to habitual behaviours that often become automatic and rigid (author unknown yet, Review of Education article, Hobbiss et al ., 2020). According to Hobbiss et al .…”
Section: Findings From the Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a different approach was not easy. This is unsurprising given that teaching is highly conducive to habitual behaviours that often become automatic and rigid (author unknown yet, Review of Education article, Hobbiss et al ., 2020). According to Hobbiss et al .…”
Section: Findings From the Teachersmentioning
confidence: 99%
“…According to Hobbiss et al . (2020) this automaticity becomes a problem with teachers ‘performing complex classroom routines with little explicit deliberation’ (n.p.). Yet we were asking our teachers to reverse their habits ; to not only consider their teaching in deliberative ways, but to shift established habits from outcomes‐based to knowledge‐informed design practice.…”
Section: Findings From the Teachersmentioning
confidence: 99%
“…Experienced teachers have between 5 and 25 years of teaching experience. System-level goals for experienced teachers are retaining experienced teachers who cultivate student learning, and continuing to equip and motivate them by fostering their continuous professional development rather than allowing them to settle into performance plateaus (Hobbiss et al, 2020). Part of retaining experienced teachers will almost certainly be compensation that rises with seniority, but not merely because of seniority per se, but because the efficacy and contributions of teachers to educational goals rise with seniority.…”
Section: Pre-servicementioning
confidence: 99%
“…We anticipated that impact on teacher practice and student learning would initially be low as teachers struggled to adopt the new pedagogical practices (Hobbiss, Sims, and Allen 2020), but that towards the end of the professional development programme and after the programme ends, there would be an impact. We would also expect this impact to deepen as teachers reteach the CA lessons they know for a second time, in the years after the professional development programme ends: research into CA has historically shown that if the intervention is carried out with the same cohort of teachers and students for two years, there is a significant and lasting impact on student learning both within and beyond the focus subject case (e.g.…”
Section: The Professional Development Programmementioning
confidence: 99%